The Control System of Friction Welding Machine for 5000kN Large Electrolytic Aluminum Prebaked Anode Conductor. Issue 5 (January 2021) - Feng, Xiaolin; Mao, Haijie; Liu, Chaorong; Liu, Manqiang
Abstract: A friction welding machine, which improves the connection performance of two different metals by generating heat of relative movement of friction, could increase the maximum contact area and lower energy and human labor consumption. The machine's control system reaches the manufacturing process's demands with its design and exerts its promising prospects.